New anamorphic powdery mildews from India - KAMAL and D.K. AGARWAL, NASIM AHMAD*, A.K. SARBHOY (Indian Phytopathology, 2004)
Powdery mildews are encountered both in their anamorphs and teleomorphs, anamorphs are encountered frequently in nature. Present study deals with the powdery mildews occurring in its anamorphic states in Northern India bordering mid-Himalayan region. Two new species and one new variety of Oidium, viz., O. lathyri, O. muehlenbeckiae and O. phyllanthi Yen var. reticulatum collected on Lathyrus odoratus L., Muehlenbeckia platyclada (F. Muell.) Meissn. and Kirganelia reticulata (Poir.) Baill. respectively, are described and illustrated.